A City With Vanishing Ambience: Virtual Architecture And Education To Help Repair Novokuznetsk’s Glory - et. al., Y S Serenkov, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Тhe article proposes an interdisciplinary approach to solving the problem of the prospects of individual cities of the Siberian region. On the basis of culturological material, with the involvement of research in the field of architecture, the author analyzes the reasons for the loss of the city of Novokuznetsk of its former representative appearance. Among the factors that contributed to the city's loss of the status of a convenient, comfortable place to live, along with the economic and environmental components, the city's atmosphere, created, among other things, by the architectural landscape, stands out. Despite the fact that urban architecture still has undoubted attractiveness against the background of nearby cities, and Novokuznetsk has, so to speak, its own “face”, nevertheless, some important “traces” in the cultural and historical heritage have been lost today. Thus, the article makes an excursion into the cultural and historical past of the southern capital of Kuzbass, which makes it possible to draw a conclusion about its worthy cultural potential, which can become the basis for the revival of its former glory and outline the prospects for further development. On the basis of research in the field of architecture and pedagogy, the possibility of "immersion" in the architectural atmosphere of the lost monuments of architecture in order to develop the ambient environment of the city is substantiated and a comprehensive model of such "restoration" by means of modern technologies is proposed. The concept of virtual architecture proposed by the authors of the article is interesting from the point of view of its contribution not only to local history, but also as one of the attractive, relevant and understandable for modern youth ways of immersion in the history and modern life of their city, cultural and educational leisure. The study, in general, outlines the development of one of the most relevant today multidisciplinary scientific areas at the intersection of pedagogy, cultural studies and architecture, contributing to the solution of a number of both theoretical and applied problems.